الجامعة الجزائرية وسؤال الحرية الأكاديمية: مقاربة نظرية في ضوء متغيرات الواقع - العيفة, سالمي (جامعة الوادي University of Eloued, 2019)
الملخص: تهدف هذه الورقة إلى تسليط الضوء على حقيقة الحرية الأكاديمية في الجامعة الجزائرية ، واعتماد نهج نظري قائم على ، والحرية كمبدأ إنساني مستقر ، لا يمكن تحقيقها أكاديميا فقط ضمن شروط ومتطلبات المجتمع الأكاديمي من خلال إعادة تأسيس مفهوم الحرية الأكاديمية نفسها. يتضمن هذا البحث محورين ، الأول مكرس للمناقشة المفاهيمية حول أهمية الموضوع ، حتى استكشاف موقعه في اللوائح والمواثيق الدولية للتأكيد على أهمية المفهوم في المجتمع الأكاديمي. الموضوع الثاني يدور حول واقع الحرية الأكاديمية في الجامعة الجزائرية ، وذلك باستخدام مؤشرات للتشكيك في القانون والواقع. Abstract: This paper aims to shed light on the reality of academic freedom at the Algerian University, adopting a theoretical approach based on, freedom as a stable human principle, can’t be achieved academically only within the conditions and requirements of the academic community by re-establishing the concept of academic freedom itself. This research involves two axes, the first one is devoted for the conceptual- Significance discussion about the subject, even exploring its position in international regulations and charters to emphasize the importance of the concept in the academic community. The second topic is about the reality of academic freedom at the Algerian University, using indicators to question both the law and reality.
The Algerian University And The Question Of Academic Freedom: A Theoretical Approach In The Light Of The Variables Of Reality
Keywords: الحرية الأكاديمية، الجامعة، المجتمع الأكاديمي; academic freedom ; University ; Academic community